NYPD Red 3 - Patterson, James, 1947-; Karp, Marshall; Ballerini, Edoardo, 1970-; Green, Dan, 1975-; Smith, Cheryl; Hachette Audio (Firm) ([New York] : Hachette Audio, 2015)
Hunter Alden, Jr., a billionaire businessman, has it all: a sexy wife, a brilliant teenage son, and an ever-growing fortune. But his perfect life shatters one horrific night when he discovers the severed head of his chauffeur, stuffed in a bag marked, in blood, with his son's initials. Now his son is missing, and the price to get him back might be too high; even for one of the world's richest men.
Keywords: Police -- Fiction -- New York (State); Murder -- Fiction -- Investigation -- New York (State); Billionaires -- Fiction -- New York (State); Missing persons -- Fiction -- New York (State); Audiobooks; Suspense fiction; Audiobooks